Tradisi Lisan Kinoho/Lolamoa (Pantun): - Sutiyana Fachruddin; Asriani . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT Every indigeneous culture is an asset that has a value that should be in the preserve history, passed down continuously from one generation to the next. Oral Tradition as a culture heritage can be used as one of the entrances to further understand the people and their culture. Oral Tradition should be used at the present time to revive the values of good for people in their life. An important role of tradition in a society lies in its ability to communicate the tradition, knowledge, and certain etnic custom, or can be describe human experiences in both individual and social dimension, to the other ethnic groups. This oral tradition consisted of several forms, such as rhyme. For the people of Tolaki, rhyme reffered to as kinoho or lolamoa. This verse is usually delivered in a traditional ceremony, reception as guests at the wedding or government guests who come to visit. Kinoho or lolamoa contains satire, advices, oath and covenant. Key words: rhyme, lokal wisdom message, oral tradition, people of etnic Tolaki